Jane Austen's Families - Sturrock, Jane (Anthem Press, 2013)
"Jane Austen's Families" focuses on family dynamics in Jane Austen's six novels. After a general introduction, which places its approach in the context of ethical criticism, it divides into two sections. The first, "Family Dynamics," consists of three chapters - "The Function of the Dysfunctional Family," "Spoilt Children" and "Usefulness and Exertion." The three chapters of section two, "Fathers and Daughters," look at father-daughter relationships in "Mansfield Park," "Emma" and "Persuasion."